The burnout syndrome: Historical evolution since the employment context to the sports field - Carlin, Maicon; Garcés de los Fayos Ruiz, Enrique J. (Anales de Psicología / Annals of Psychology, 2010)
Studies conducted on the burnout Syndrome began to be de-veloped in the mid-70s, researchers concerned with the occupational health of workers engaged too demanding. These skills were transferred to the sports field at the beginning of the 80s, to explain the evil that afflicted a large quantity of athletes. Those individuals without symptoms charac-terized by emotional exhaustion, depersonalization and reduced personal achievement. This consequently, led to a progressive decrease in their levels of athletic performance, to cause a premature withdrawal from the sport. Years later, theoretical models were created with the aim to explain certain parameters of the burnout Syndrome in athletes. This paper offers a historical review of the burnout, from labor to the sports context.